2020
DOI: 10.1371/journal.pone.0229194
|View full text |Cite
|
Sign up to set email alerts
|

Area per player in small-sided games to replicate the external load and estimated physiological match demands in elite soccer players

Abstract: The current study determined the area-per-player during small-or large-sided games with or without goalkeeper that replicates the relative (m�min-1) total distance, high-intensity running distance, sprint distance and metabolic power covered during official matches. Time-motion analysis was performed on twenty-five elite soccer-players during 26 home-matches. A total of 2565 individual samples for SSGs using different pitch sizes and different number of players were collected and classified as SSGs with (SSG-G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
145
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 69 publications
(162 citation statements)
references
References 47 publications
(112 reference statements)
15
145
1
1
Order By: Relevance
“…Rampinini et al [5] found an increase on both RPE and heart rate in the large than both medium and small pitches. Moreover, the increased external load in the large pitch showed by our results (i.e., TD: g = 1.59; MSD: g = 1.03; HSD: g = 2.27; VHSD: g = 1.38; average speed: g = 1.55; maximal speed: g = 1.18) confirmed those of previous studies [6,8,19,21]. For example, Casamichana et al [21] compared three pitches of different size, finding that external load metrics increased as the pitch size became wider, especially comparing large to small pitches.…”
Section: Pitch'size Effectsupporting
confidence: 92%
See 4 more Smart Citations
“…Rampinini et al [5] found an increase on both RPE and heart rate in the large than both medium and small pitches. Moreover, the increased external load in the large pitch showed by our results (i.e., TD: g = 1.59; MSD: g = 1.03; HSD: g = 2.27; VHSD: g = 1.38; average speed: g = 1.55; maximal speed: g = 1.18) confirmed those of previous studies [6,8,19,21]. For example, Casamichana et al [21] compared three pitches of different size, finding that external load metrics increased as the pitch size became wider, especially comparing large to small pitches.…”
Section: Pitch'size Effectsupporting
confidence: 92%
“…The presence of two additional players (two goalkeepers) had probably a greater relative weight in the small pitch than in the large one. Similar results were found by Gaudino et al [8] and Riboli et al [6], however, a comparison can be flawed because in their study the use of several formats and rules may have influenced the effect of interaction between the presence of goalkeepers and the dimension of the pitch. On the contrary, Hulka et al [16] found that the distance covered was higher with goalkeepers than without in small pitch and no differences were found in medium and large pitches.…”
Section: Pitch' Size and Goalkeepers' Presence Interactionsupporting
confidence: 70%
See 3 more Smart Citations